Influence of solvents on characteristics of nanoparticles prepared by pulsed laser ablation on iron target - Htain Lin Aye (2018)
An iron target submerged in three different solvents (distilled water, absolute ethanol and acetone) was laser ablated to study the influence of solvents on the size and composition of the nanoparticles produced. A Nd:YAG laser ablation machine was operated at wavelength 1064 nm, pulse power 90 W, pulse frequency 30 kHz and pulse duration 3 ns. Nanoparticles were characterized by UV-Vis spectroscopy and transmission electron microscopy (TEM). TEM revealed that spherical nanoparticles, mainly FeO, were observed in all solvents. Fe2O3 was found only in distilled water. Well-dispersed nanoparticles with mono-modal distribution and a mean particle size of ca. 20 nm were produced only in the acetone. It is believed that higher dipole moment of the solvents should lead to an inhibition of growth or aggregation of nanoparticles, and hence the smallest nanoparticles were observed with the acetone.